Mitochondrially targeted vitamin E succinate modulates expression of mitochondrial DNA transcripts and mitochondrial biogenesis - Truksa, Jaroslav; Dong, Lan-Feng; Rohlena, Jakub; Stursa, Jan; Vondrusova, Magdalena; Goodwin, Jacob; Nguyen, Maria; Kluckova, Katarina; Rychtarcikova, Zuzana; Lettlova, Sandra; Spacilova, Jana; Stapelberg, Michael; et al. (Antioxidants & redox signaling, 2015)
AIMS: To assess the effect of mitochondrially targeted vitamin E (VE) analogs on mitochondrial function and biogenesis. RESULTS: Mitochondrially targeted vitamin E succinate (MitoVES) is an efficient inducer of apoptosis in cancer cells. Here, we show that unlike its untargeted counterpart α-tocopheryl succinate, MitoVES suppresses proliferation of cancer cells at sub-apoptotic doses by way of affecting the mitochondrial DNA (mtDNA) transcripts. We found that MitoVES strongly suppresses the level of the displacement loop transcript followed by those of mtDNA genes coding for subunits of mitochondrial complexes. This process is coupled to the inhibition of mitochondrial respiration, dissipation of the mitochondrial membrane potential, and generation of reactive oxygen species. In addition, exposure of cancer cells to MitoVES led to decreased expression of TFAM and diminished mitochondrial biogenesis. The inhibition of mitochondrial transcription was replicated in vivo in a mouse model of HER2(high) breast cancer, where MitoVES lowered the level of mtDNA transcripts in cancer cells but not in normal tissue. INNOVATION: Our data show that mitochondrially targeted VE analogs represent a novel class of mitocans that not only induce apoptosis at higher concentrations but also block proliferation and suppress normal mitochondrial function and transcription at low, non-apoptogenic doses. CONCLUSIONS: Our data indicate a novel, selective anti-cancer activity of compounds that act by targeting mitochondria of cancer cells, inducing significant alterations in mitochondrial function associated with transcription of mtDNA-coded genes. These changes subsequently result in the arrest of cell proliferation.
Keywords: mitochondriální DNA; DNA, Mitochondrial; Mitochondria; Neoplasms; Cell Line, Tumor; Cell Proliferation; alpha-Tocopherol; reaktivní formy kyslíku; Cell Respiration; buněčné dýchání; receptor erbB-2; alfa-tokoferol; Reactive Oxygen Species; Receptor, ErbB-2; Animals; lidé; myši transgenní; Humans; zvířata; Mice, Transgenic; myši; apoptóza; proliferace buněk; membránový potenciál mitochondrií; nádory; nádorové buněčné linie; Mice; Membrane Potential, Mitochondrial; mitochondrie; Apoptosis